THE THERMODYNAMIC MODELING OF THE URANIUM-OXYGEN SYSTEM - Basuki Agung Pudjanto (Jurnal Teknologi Bahan Nuklir, 2005)
ABSTRACT THE THERMODYNAMIC MODELING OF THE URANIUM-OXYGEN. The thermodynamic modeling of the uranium-oxygen (U−O) system, which is of first importance in the development of a nuclear thermodynamic database, has been performed. The thermodynamic properties of the phases present in the U−O system are described using the compound energy model with ionic constituents for the solids and an ionic twosublattice model for the liquid. For the uranium dioxide, the structure is described using three sublattices, one for the cations U3+, U4+ and U6+, one for the normal site of oxygen ions, and one for the interstitial oxygen ions. Vacancies are included in both oxygen sublattices. In this first approach, the homogeneity ranges of the U4O9-y and U3O8-y compounds are not represented. Phase diagram and thermodynamic properties, then, have been calculated from the optimized Gibbs energy parameters, assuming that the system is in thermodynamic equilibrium, i.e. by finding the minimum for the total free energy of the system. The thermodynamic calculation is conducted through CALPHAD (Calculation Phase Diagram) approach, with the help from the Thermo-Calc code. The results obtained show that the consistency between the calculated results and the experimental data is quite satisfactory. FREE TERMS: Nuclear fuel, Uranium oxide, Oxygen potential, Modeling, Thermodynamics ABSTRAK PEMODELAN TERMODINAMIK SISTEM URANIUM-OKSIGEN. Pemodelan termodinamik sistem uranium-oksigen (U−O), yang penting sekali bagi pengembangan database termodinamik nuklir, telah dilakukan. Sifat-sifat termodinamik fasa-fasa yang ada dalam sistem U−O diGambarkan menggunakan model ‘energi senyawa’ dengan model ‘konstituen ionik’ untuk fasa-fasa padat dan model ‘dua sub-lapis ionik’ untuk fasa cair. Sementara itu, struktur uranium dioksida diGambarkann dengan model ‘tiga sub-lapis ionik’, satu sub-lapis untuk kation U3+, U4+ dan U6+, satu sub-lapis untuk kisi normal ion-ion oksigen dan satu sub-lapis lagi untuk interstisi ion-ion oksigen. Kekosongan-kekosongan dimasukkan ke dalam kedua sub-lapis oksigen. Pada kajian awal ini, rentang homogenitas senyawa U4O9-y dan U3O8-y tidak diberikan. Selanjutnya, diagram fasa dan sifat termodinamik dihitung dari optimasi parameter energi Gibbs, dengan asumsi bahwa sistem berada dalam kesetimbangan termodinamik, yaitu dengan mencari harga minimum dari energi bebas total sistem. Perhitungan dilakukan dengan pendekatan metode CALPHAD, dengan bantuan paket program Thermo-Calc. Hasil yang diperoleh menunjukkan konsistensi yang cukup memuaskan antara hasil perhitungan dan data eksperimen. KATA KUNCI: Bahan bakar nuklir, Uranium oksida, Potensial oksigen, Pemodelan, Termodinamika